Adoption of Hardship Clauses in Indonesia's Contract Law Reform System - Ensalina Papilaya; Sari Murti Widiyastuti; Husni (International Journal of Law, Social Science, and Humanities, 2026)
Adoption of hardship clause in the Indonesian contract law system. This thesis is written with the aim of understanding how judges in Indonesia resolve (hardship) or difficult circumstances that arise during the execution of contracts. The research method used is a normative approach with data collection through literature studies, interviews with legal practitioners, and document analysis. The results show that the adoption of hardship clauses can provide flexibility in agreements faced with unforeseen situations, but requires the establishment of clear regulations and a good understanding by legal practitioners in order to be implemented effectively. This research is expected to make a significant contribution to the development of contract law in Indonesia by facilitating justice and legal certainty in contractual practice. Keywords, hardship clause , Contract, Justice, Indonesian Legal System